2018
DOI: 10.1148/radiol.2018180070
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small Cell Lung Cancer with Resistance to EGFR-TKI Therapy: CT Characteristics of T790M Mutation–positive Cancer

Abstract: Purpose To evaluate the clinical and CT characteristics of T790M mutation-positive non-small cell lung cancer (NSCLC) after epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) therapy failure. Materials and Methods A retrospective study of 304 patients with NSCLC who underwent rebiopsy after first-line EGFR-TKI therapy was conducted. Rebiopsy methods included CT- or fluoroscopy-guided lung biopsies (n = 105), endobronchial US- or bronchofibroscopy-guided biopsies (n = 66), pleural fluid ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“…We showed, for the first time in a Caucasian population, that age younger than 65 and exon 19 deletion as baseline sensitizing mutation were significantly correlated with acquired T790M mutation at the time of disease progression. Several studies previously investigated age as a clinical factor potentially correlated with T790M mutation, without significant findings in most cases 33,41 ; on the contrary, a Japanese case series showed a positive correlation in patients older than 75 years, but the median age in this patient population was older than our series. 37 Our results are in line with other case series that previously confirmed a correlation between exon 19 deletion and acquisition of T790M mutation probably because of a longer selective pressure of EGFR TKIs in more sensitive mutations.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…We showed, for the first time in a Caucasian population, that age younger than 65 and exon 19 deletion as baseline sensitizing mutation were significantly correlated with acquired T790M mutation at the time of disease progression. Several studies previously investigated age as a clinical factor potentially correlated with T790M mutation, without significant findings in most cases 33,41 ; on the contrary, a Japanese case series showed a positive correlation in patients older than 75 years, but the median age in this patient population was older than our series. 37 Our results are in line with other case series that previously confirmed a correlation between exon 19 deletion and acquisition of T790M mutation probably because of a longer selective pressure of EGFR TKIs in more sensitive mutations.…”
Section: Discussioncontrasting
confidence: 94%
“…Evidence about clinical features of patients with EGFR mutations potentially predicting the acquisition of T790M mutation is currently limited and mostly available on Asian patients. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] This clinical scenario would hopefully help to select the right strategy for every patient, considering the availability of a thirdgeneration TKI both as a firstand second-line treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this era of targeted therapy, it would be critical to obtain adequate tissue samples not only for a pathologic diagnosis but also for genetic analysis for the management of patients with lung cancer (21). Although several studies (22)(23)(24)(25)(26) reported that the diagnostic yield of PTNB for mutational analysis was 78.8%-96.7%, the yield of adequate tissue for mutational analysis according to different needle types, sizes, and number of tissue samplings remains unclear and needs to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Koo et al retrospectively studied 304 patients with NSCLC who underwent re-biopsy after administration of first-line EGFR-TKI therapy (13). They analyzed computed tomography (CT) findings at the initial diagnosis and those at re-biopsy and attempted to reveal the radiological features of lesions with T790M mutation.…”
mentioning
confidence: 99%